1998
DOI: 10.1007/s11745-998-0235-5
|View full text |Cite
|
Sign up to set email alerts
|

Modification of milk formula to enhance accretion of long‐chain n−6 and n−3 polyunsaturated fatty acids in artificially reared infant rats

Abstract: Artificially reared infant rats were used to determine the effects of long-chain polyunsaturated fatty acid (LCPUFA) supplementation on blood and tissue concentrations of arachidonic acid (AA) and docosahexaenoic acid (DHA). Beginning at 7 d of age, infant rats were fed for 10 d with rat milk formulas supplemented with AA at 0, 0.5 and 1.0%, or supplemented with DHA at 0, 0.5 and 1.0% of total fatty acid. The supplementation of AA increased accretion of the fatty acid in tissue and blood phospholipids with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Seven studies were identified that measured brain concentrations of ARA and DHA following feeding of different levels of ARA during early life [33,34,[56][57][58][59][60] (Table 2a).…”
Section: Changes In Dietary Arachidonic Acid and Effect On Brain Aracmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies were identified that measured brain concentrations of ARA and DHA following feeding of different levels of ARA during early life [33,34,[56][57][58][59][60] (Table 2a).…”
Section: Changes In Dietary Arachidonic Acid and Effect On Brain Aracmentioning
confidence: 99%
“…Five studies reported lower levels of brain ARA in the groups fed lower levels of dietary ARA [56][57][58][59][60], whereas two studies detected no difference between the low and high groups [33,34]. Both studies that found no difference introduced rat dams to the diets at postnatal day (PND) 2 and measured the fatty acid composition of the pup brains at PND 15.…”
Section: Changes In Dietary Arachidonic Acid and Effect On Brain Aracmentioning
confidence: 99%
See 1 more Smart Citation
“…This dietary n-3 FA deficiency profile consists of decreased levels of DHA and increased levels of 22:4 n-6 and 22:5 n-6 and the maintenance of the total n-3 plus n-6 FA in membrane phospholipids (10). Contrariwise, the FA profile of dietary DHA supplementation over a previous n-3 deficiency had also been described in different tissues (11)(12)(13). DHA deficiency is related to learning disturbances in humans (14) and rats (15), and, on the contrary, DHA supplementation is related to learning improvement in some animal models (16).…”
mentioning
confidence: 99%
“…Maternal diet has an important influence on FA composition of milk (3) and, consequently, on FA profiles of plasma and red blood cells (RBC) of infants (4,5). Maternal diet has an important influence on FA composition of milk (3) and, consequently, on FA profiles of plasma and red blood cells (RBC) of infants (4,5).…”
Section: Introductionmentioning
confidence: 99%